Innovation in Islamic Religious Education in The Digital Era for Students' Religious Tolerance Character Building in Elementary School: An Implementation of Beyond the Wall Learning Model - Elga Yanuardianto; Djoko Rohadi Wibowo; Prima Cristi Crismono (JIP Jurnal Ilmiah PGMI, 2024)
The digital era has brought significant changes to various aspects of life, including education. This article explores innovations in Islamic religious education that leverage digital technology to foster religious tolerance among students. Through the "Beyond the Wall" learning model, which includes the use of educational applications, e-learning platforms, and augmented reality (AR) and virtual reality (VR) technologies, the learning process becomes more interactive, personalised, and contextual. This study uses a qualitative case study method at SDN Tempurejo 2 Jember, which has integrated technology into Islamic religious education. The results indicate that the use of digital technology not only enhances student engagement and understanding of the subject matter but also effectively internalises values of religious tolerance. Interfaith interactions through collaborative projects and dialogue forums help students understand and appreciate differences, build solidarity, and develop a strong attitude of tolerance. The main challenges faced are the digital divide, the need for teacher training, and issues of digital security and ethics. With the right strategies, this learning model can be an effective solution for shaping students' character to be more tolerant and appreciative of diversity in the digital era. This study uses data collection techniques involving in-depth interviews with teachers, students, and parents, as well as direct observations of the learning process at SDN Tempurejo 2 Jember. Additionally, documentation in the form of video recordings and field notes was used to explore the dynamics of student interactions in a technology-based collaborative project. The collected data were analyzed using a thematic analysis approach, where the data were grouped into key themes related to understanding religious tolerance, the use of technology in learning, and the challenges faced. This analysis also includes mapping student involvement in collaborative projects and dialogue forums. To ensure the validity of the data, this study employed source triangulation, which compares the results of interviews, observations, and documentation. Furthermore, member checking was carried out by requesting confirmation from informants to ensure the accuracy of the collected data. External validity was also tested by comparing the findings of this study with relevant literature on the use of technology in Islamic religious education.